2011
DOI: 10.1093/molbev/msr041
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Cyanophage Genomes Which Contain Mitochondrial DNA Polymerase

Abstract: DNA polymerase γ is a family A DNA polymerase responsible for the replication of mitochondrial DNA in eukaryotes. The origins of DNA polymerase γ have remained elusive because it is not present in any known bacterium, though it has been hypothesized that mitochondria may have inherited the enzyme by phage-mediated nonorthologous displacement. Here, we present an analysis of two full-length homologues of this gene, which were found in the genomes of two bacteriophages, which infect the chlorophyll-d containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Filee et al (34) previously hypothesized that it was of bacteriophage origin on the basis of weak bootstrap support for clustering with T7-like DNA polymerases. Our findings, together with those of Chan et al (35), provide strong evidence for the bacteriophage origin of the mitochondrial DNA polymerase gene. However, our analysis indicates that this is likely to have been a phage ancestral to either or both the TIM5-like myoviruses and the Acaryochloris siphoviruses, rather than to T7-like podoviruses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Filee et al (34) previously hypothesized that it was of bacteriophage origin on the basis of weak bootstrap support for clustering with T7-like DNA polymerases. Our findings, together with those of Chan et al (35), provide strong evidence for the bacteriophage origin of the mitochondrial DNA polymerase gene. However, our analysis indicates that this is likely to have been a phage ancestral to either or both the TIM5-like myoviruses and the Acaryochloris siphoviruses, rather than to T7-like podoviruses.…”
Section: Discussionsupporting
confidence: 86%
“…Chan et al (35) suggested that environmental sequences clustering phylogenetically with mitochondrial and Acaryochloris siphovirus DNA polymerase sequences may come from a phage or the bacterial ancestor of the mitochondria. These sequences cluster with S-TIM5 and have amino acid identities of 45-98% to that of S-TIM5 (Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic mitochondrial polA polymerases, which are thought to have been phage derived (37), are known from crystal structure analysis (38) to have large thumb domain inserts. The phages most similar to mitochondrial polA polymerases, A-HIS1 and -2 and S-TIM5 (39,40), also have insertions in that position. Not all phage clades had thumb inserts.…”
Section: Resultsmentioning
confidence: 99%
“…DNA pol. ), in parentheses, were not included in the tree-making computation but are marked on the figure in the position previously determined (39). Each phage is labeled as to family (p, podovirus; s, siphovirus; m, myovirus) either individually or on a branch leading to a group.…”
Section: Resultsmentioning
confidence: 99%
“…Relationship with DNA polymerase g Recent studies have reported that genes with homology to mitochondrial DNA polymerase g are abundant within the virioplankton have been found in cyanophage genomes and the Global Ocean Survey data set (Chan et al, 2011;. To determine the prevalence of these polymerases in our metagenomic libraries the VIROME databank was queried with the set of S15 DNA pol g sequences from the mitochondria, cyanophage and the Global Ocean Survey Yooseph et al, 2007) and BroadPhage (John et al, 2011) data sets (BLASTP E-score p10 À 10 ).…”
Section: Discussionmentioning
confidence: 99%